2019
DOI: 10.1007/s10648-019-09510-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Peer Assessment on Academic Performance: A Meta-analysis of Control Group Studies

Abstract: Peer assessment has been the subject of considerable research interest over the last three decades, with numerous educational researchers advocating for the integration of peer assessment into schools and instructional practice. Research synthesis in this area has, however, largely relied on narrative reviews to evaluate the efficacy of peer assessment. Here, we present a meta-analysis (54 studies, k = 141) of experimental and quasiexperimental studies that evaluated the effect of peer assessment on academic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
124
3
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(150 citation statements)
references
References 99 publications
12
124
3
11
Order By: Relevance
“…The results suggested that, when Arab EFL learners received peer assessment idea, they can effectively develop their English writing skills. This finding is in line with previous studies conducted by Hegg et al [2] and Double et al [25]. Double et al [25] recommended that peer assessment effect comes from assessing, better than being assessed and giving and receiving feedback can help students to develop their writing skills.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results suggested that, when Arab EFL learners received peer assessment idea, they can effectively develop their English writing skills. This finding is in line with previous studies conducted by Hegg et al [2] and Double et al [25]. Double et al [25] recommended that peer assessment effect comes from assessing, better than being assessed and giving and receiving feedback can help students to develop their writing skills.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in line with previous studies conducted by Hegg et al [2] and Double et al [25]. Double et al [25] recommended that peer assessment effect comes from assessing, better than being assessed and giving and receiving feedback can help students to develop their writing skills. In addition, this study is not in line with study done by Liu et al [26] stated that EFL students from other educational background could show different models of engaging in peer assessment.…”
Section: Discussionsupporting
confidence: 90%
“…Reading of the papers excluded seven papers that were reviews (Brown, 2011;Double et al, 2020;McMillan, 2016McMillan, , 2019Van der Kleij & Lipnevich, 2020;Vogl & Pekrun, 2016, Wise & Smith, 2016, five that had no measure of student perceptions of assessment (Babaii & Adeh, 2019;Chen & Lin, 2020;Gordienko, 2015;Natsis et al, 2018;Taghizadeh & Kazemzadeh, 2019), one…”
Section: Methodsmentioning
confidence: 99%
“…Besides, feedback can also be given from student to student or peer assessment. The implementation of peer assessment is a proven ability to help students in increasing their academic ability (Double, McGrane, & Hopfenbeck, 2020). Specifically, it is also related to increasing the writing ability of the students.…”
Section: Introductionmentioning
confidence: 99%